Echocardiographic screening for subclinical rheumatic heart disease: Improving screening through simplification of the diagnostic criteria - Hunter, Luke David (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.